Sandworms of Dune - Herbert, Brian; Anderson, Kevin J., 1962- (London : Hodder, 2008)
Based upon Frank Herbert's final outline, presents the last of the Dune series which reveals the future of the planet Arrakis, the final revelation of the Kwisatz Haderach, and the resolution to the war between man and machine.
"Based on an outline by Frank Herbert."
Adult.
Adult
Keywords: Dune (Imaginary place) -- Fiction; Life on other planets -- Fiction; Robots -- Fiction; Dune (Imaginary place) -- Fiction; Life on other planets -- Fiction; Robots -- Fiction; Science fiction; Science fiction